Down regulation of the TCR complex CD3 ζ-chain on CD3+ T cells: a potential mechanism for helminth mediated immune modulation - Appleby, Laura J.; Nausch, Norman; Bourke, Claire D.; Mutapi, Francisca; Midzi, Nicholas; Mduluza, Takafira; Allen, Judith; Heard, Francesca; Erskine, Louise (Frontiers in Immunology, 2015)
The CD3ζ forms part of the T cell receptor (TCR) where it plays an important role in coupling antigen recognition to several intracellular signal-transduction pathways leading to T cell effector functions. Down regulation of CD3ζ leads to impairment of immune responses including reduced cell proliferation and cytokine production. In experimental models, helminth parasites have been shown to modulate immune responses directed against them and unrelated antigens, so called bystander antigens, but there is a lack of studies validating these observations in humans. This study investigated the relationship between expression levels of the TCR CD3ζ chain with lymphocyte cell proliferation during human infection with the helminth parasite, Schistosoma haematobium, which causes uro-genital schistosomiasis. Using flow cytometry, peripheral blood mononuclear cells (PBMCs) from individuals naturally exposed to S. haematobium in rural Zimbabwe were phenotyped, and expression levels of CD3ζ on T cells were related to intensity of infection. In this population, parasite infection intensity was inversely related to CD3ζ expression levels (p < 0.05), consistent with downregulation of CD3ζ expression during helminth infection. Furthermore, PBMC proliferation was positively related to expression levels of CD3ζ (p < 0.05) after allowing for confounding variables (host age, sex, and infection level). CD3ζ expression levels had a differing relationship between immune correlates of susceptibility and immunity, measured by antibody responses, indicating a complex relationship between immune activation status and immunity. The relationships between the CD3ζ chain of the TCR and schistosome infection, PBMC proliferation and schistosome-specific antibody responses have not previously been reported, and these results may indicate a mechanism for the impaired T cell proliferative responses observed during human schistosome infection.